Basketball Camp Champ - Jake Maddox (Stone Arch Books, 2020)
After only ever playing pick-up games, Ana Ramirez is excited to attend a basketball summer camp where she'll play on a real team with real teammates. But when the coach says they'll use something called zone defense, the shooting guard feels totally lost and starts to doubt her skills. Can Ana get out of her comfort zone and ask for help?
Keywords: Sports Stories -- Sports Stories